Reações ácido-base: conceito, representação e generalização a partir das energias envolvidas nas transformações - Pastre, Iêda Aparecida [UNESP]; Plicas, Lídia Maria de Almeida [UNESP]; Tiera, Vera Aparecida de Oliveira [UNESP]; Custódio, Juliana Vieira; Agostinho, Silvia Maria Leite (Sociedade Brasileira de Química, 2012)
Undergraduate students on the first year of Chemistry Courses are unfamiliar with the representation of acid-base reactions using the ionic equation H+ + OH- → H2O. A chemistry class was proposed about acid-base reactions using theory and experimental evaluation of neutralization heat to discuss the energy involved when water is formed from H+ and OH- ions. The experiment is suggested using different strong acids and strong base pairs. The presentation of the theme within a chemistry class for high school teachers increased the number of individuals that saw the acid-base reaction from this perspective.
Acid-base reactions: concept, representation and generalization from the energy involved in transformations
Keywords: acid-base reactions; neutralization heat; ionic equation